Oyster shell-derived nano-hydroxyapatite and proanthocyanidin pretreatment on dentinal tubule occlusion and permeability before and after acid challenge—an in vitro study - Bhavan Ram, Udatha; Sujatha, Venkatappan; Vidhya, Sampath; Jayasree, Raghavan; Mahalaxmi, Sekar (Journal of materials science. Materials in medicine, 2023)
This in vitro study evaluated the dentinal tubule occlusion (TO), depth of penetration (DoP), and dentin permeability (DP) of oyster shell-derived nanohydroxyapatite (os-nHAp) with and without 15% proanthocyanidin (PA) pretreatment. os-nHAp was synthesized via the precipitation method and it was characterized. The morphology and particle size of os-nHAp were analyzed using a high-resolution transmission electron microscope (HRTEM). Cytotoxicity of os-nHAp, PA/os-nHAp, and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) was assessed by (3-(4,5-dimethythiazol-2-yl) 2,5-diphenyl tetrazolium bromide (MTT) assay using human osteosarcoma (MG-63) cell line. One hundred and ninety-seven dentin discs of 3 mm thickness were prepared from the crown portion of extracted human teeth. The dentinal surfaces of the discs were etched for 2 min with 6% citric acid to simulate dentin hypersensitivity. Five discs were randomly selected and the patency of dentinal tubules was confirmed using a scanning electron microscope (SEM). The remaining 192 discs were divided into four groups ( n = 48) depending on the type of remineralization as follows: group 1: os-nHAp, group 2: PA/os-nHAp, group 3: CPP-ACP, and group 4: no treatment. The remineralization protocol was followed for 21 days. Out of the 48 dentin discs in each group, 32 discs were used to evaluate dentinal tubule occlusion (TO) and depth of penetration (DoP) using SEM. The remaining 16 discs were subjected to an assessment of dentin permeability (DP) using a hydraulic conductance model. TO, DoP and DP were evaluated after remineralization and acid challenge. Characterization studies confirmed the presence of pure phase apatite. HRTEM confirmed the nanometric particle size of os-nHAp. MTT assay results showed that all the tested materials exhibited >80% cell viability when tested up to a concentration of 100 µg/mL. The results demonstrated a significantly higher mean percentage of TO, DoP, and lesser mean DP after remineralization in groups 1, 2, and 3 ( p < 0.05). After the acid challenge, group 3 showed a significant reduction in TO and DoP, and increased DP ( p < 0.05). However, no such changes were observed in groups 1 and 2. Within the limitations of this study, it can be concluded that os-nHAp and PA/os-nHAp could serve as potential and durable therapeutic agents in the treatment of dentin hypersensitivity. Graphical Abstract